FACTORS OF ECONOMIC GROWTH AND THEIR PRACTICAL REFLECTION IN UZBEKISTAN - Shukurova Khayriniso Zokir qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article analyzes the concept of economic growth, its main factors, and their practical manifestation in developing countries, particularly in Uzbekistan. The impact of production factors, technological progress, investments, human capital, and institutional environment on economic growth is examined. The results of economic reforms are evaluated based on real statistical data, and proposals for ensuring sustainable growth are presented.